Effect of Addition Cinnamon (Cinnamomum verum) Levels of Moisture Content, Ash Content, and Protein Content of Sea Grape Instant Drink (Caulerpa sp) - Heatubun, Amelia (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2023)
It is believed that instant beverages are convenient, quick to make, and have a long shelf life because they often come in the form of powdered granules that are easily soluble in water when applied. The community’s main draw for instant beverage items in powder form is their ease of preparation and consumption. Instant drinks commonly include additives and flavor enhancers to boost nutritional content or improve aroma. The purpose of this study was to describe the results of increasing the cinnamon juice concentration during the production of instant sea grape drinks. In this study, five levels of cinnamon extract concentrations 0, 1, 2, 3, and 4% were used in a completely randomized experimental design. The results demonstrated that adding cinnamon juice to instant sea grapes (Caulerpa sp) drinks resulted in a decrease in moisture content of 3.8 to 0.97%, an increased ash content ranges from 1.5 to 2.40%, and protein content of 1.92-2.05%.